Implementation of Playwright as an Automation Tool for Functional Web Application Testingon Tool for Functional Web Application Testing - Nurbilkis, Gina; Sujjada, Alun (Society : Jurnal Pengabdian Masyarakat, 2026)
The rapid development of web technology has increased the complexity of modern applications, requiring efficient and accurate testing methods. PT. Neuronworks Indonesia previously used manual and semi-automated testing through the Cypress framework, which has limitations in cross-browser support and script maintenance. To address these issues, a community service activity was carried out by implementing the Playwright framework as a tool for functional web application test automation. The activity included training, test environment preparation, and direct implementation on the company’s web project. The results showed an improvement in regression testing efficiency from around three hours to one hour per cycle. Test stability and consistency increased by approximately 20% with the support of multi-tab features and cross-browser testing. This activity not only improved testing performance but also strengthened the QA staff’s technical competence in using modern automation tools. The implementation of Playwright proved effective in optimizing the quality assurance process and is recommended for broader adoption in web application testing within the industry.